A single-phase tri-state integrated Buck-Boost inverter suitable to operate in grid-connected and island modes - Pena, Jose Carlos U. [UNESP]; Canesin, Carlos A. [UNESP]; Guzman, Cindy P.; IEEE (Ieee, 2016)
This paper introduces a methodology to model and control a single-phase tri state integrated Buck-Boost inverter suitable for low power distributed generation with the capability to operate in grid connected and island modes. The tri-state modulation is adopted in order to achieve power decoupling by means of average inductor current. This way it is possible to control the DC/AC conversion independently of the input current. The proposed strategy considers a multiple loop control scheme, where controllers are tuned based on a linearized models of the system. Main experimental results from a 300W prototype are included and discussed.
Keywords: microinverters; distributed generation; grid-tie and island modes; renewable energies